Community Empowerment KWT"Bengke Sakato" Pariaman With Innovation of VCO Process Waste Converted into Bags and Tiles: Pemberdayaan Masyarakat KWT”Bengke Sakato” Pariaman Dengan Inovasi Limbah Proses VCO Diubah menjadi Tas dan Ubin - Suryani, Suryani; Rafnelly Rafki; Rahmawati; Yuliesi Purnawati; Sevindrajuta; Yustitia Akbar; Afdhal Rinsik; Verawati; Rinda Lestari (Journal of Community Service and Application of Science, 2022)
The partner of the Community Service Team chaired by Prof. Dr. Suryani, MSi is KWT "Bengke Sakato" a partner from Padang Pariaman Regency. KWT "Bengke Sakato" has long been engaged in having a Virgin Coconut Oil (VCO) production business, because in addition to the natural products where KWT is domiciled abundantly with coconut trees, this group has also been given training on how to make VCO. This VCO production waste has not been maximized, even though the waste such as coconut husk can be used as cocopeat and cocofiber, and shells can be used as charcoal, bags and tiles or tiles. The method used has several stages, namely Socialization, Workshop, Monitoring and Evaluation as well as mentoring. This program successfully trains people to make bags and tiles from coconut shells using machines provided by the Service Team. With the training of these KWT members, they process VCO waste into various products, it can increase the income of this group. From 500 coconut shells can earn Rp. 5,900,000. And can also increase his knowledge by 79.33%. Thus, this activity of service in the future can contribute to community income.